Recovery of oculomotor nerve palsy secondary to posterior communicating artery aneurysms*. (August 2014) - Patel, Krunal; Guilfoyle, Mathew R.; Bulters, Diederik O.; Kirollos, Ramez W.; Antoun, Nagui M.; Higgins, J. Nicholas P.; Kirkpatrick, Peter J.; Trivedi, Rikin A.
Abstract Background. Recent studies suggest more favourable recovery of oculomotor nerve palsy (ONP) caused by posterior communicating artery (PComA) aneurysms with microsurgical clipping compared to endovascular coiling. We describe a consecutive series of patients with ONP from PComA aneurysms treated by microsurgical clipping or endovascular coiling. Methods. We retrospectively reviewed medical records of all patients from 2005 to 2009 with complete or partial ONP from PComA aneurysms. Results. Twenty patients were identified, three with unruptured aneurysms. Two patients with ruptured aneurysms were unfit for treatment and therefore excluded. Of the 18 patients included (15 female), 9 underwent microsurgical clipping and 9 received endovascular coiling. Patients treated by surgical clipping were significantly younger compared to those treated by endovascular coiling (mean 52.3 vs. 67.9 years; p = 0.039). Five patients had incomplete ONP (3 clipped, 2 coiled) and thirteen had complete ONP. At 6 months, six of nine patients treated with clipping and five of nine patients treated with coiling had complete resolution of their ONP (p = 1.0); the remainder had partial improvement. There was no significant difference in duration of pre-treatment ONP, age, sex or status of aneurysm (ruptured or unruptured) between patients in the two groups or between those with full or partial recovery. However, all 5 patients with incomplete ONP at presentation recovered fully, compared with 6 of 13 patients who presented with complete ONP. Conclusions. We found no significant difference between clipping and coiling in the recovery of ONP due to PComA aneurysms. Patient who present with incomplete ONP are more likely to have a full recovery of ONP following either treatment modality than those who present with complete ONP.